RADIOPACITY ANALYSIS OF SOME CHAIRSIDE COMPUTER-AIDED DESIGN-COMPUTER-AIDED MANUFACTURING MILLING MATERIALS - VARVARĂ, Adrian Mihai; GASPARIK, Cristina; CULIC, Bogdan; BONDOR, Cosmina Ioana; VARVARĂ, Elena Bianca; FURTOS, Gabriel; MOLDOVAN, Marioara; DUDEA, Diana (Studia Universitatis Babeș-Bolyai Chemia, 2019)
In this study, the radiopacity of chairside Computer-Aided Design-Computer-Aided Manufacturing (CAD-CAM) milling materials was evaluated in comparison with dental structures. 105 specimens of 7 different thicknesses from 5 different types of chairside CAD-CAM milling materials: feldspar ceramic, hybrid ceramic, lithium disilicate glass-ceramic, zirconia-reinforced lithium silicate ceramic and a resin nano-ceramic were used for this in vitro study. Digital radiographs were obtained using an aluminum step wedge, a specimen of a tooth slice and 3 specimens from each material. Radiodensity was determined for each material using dedicated software. Lava Ultimate and Vita Suprinity were found as having higher radiopacity, whilst Vita Mark II and Vita Enamic were lower in radiopacity in comparison with dental structures. The radiodensity of Emax CAD was between enamel and dentine. Radiopacity of each CAD-CAM milling material was different and both material’s type and thickness significantly affected the radiopacity.